Chronometry as a Method to Assess the Formation of Skills Required for Work with the Agents of Particularly Dangerous Infections in the Course of Professional Retraining - E. V. Sazanova; T. A. Malyukova; A. V. Boiko; E. V. Rastuntseva; E. Yu. Lotsmanova; Z. S. Yusupova (Проблемы особо опасных инфекций, 2011)
The aim of the study is to assess how successfully the trainees obtain skills of post mortem examination of laboratory animals, with strict observance of the rules of safe work with pathogenic biological agents of I-II groups, during their training at professional retraining courses. Individual continuous chronometry is offered as the assessment method. The obtained results can be used for planning of practical training, drafting the time-table, standardization of work of instructors.